Genetically modified ecosystems: Innovative approaches in agriculture and their environmental impact - Choriyeva Zebiniso (BIO Web of Conferences)
The exploration of genetically modified ecosystems in agriculture has evolved significantly, presenting innovative solutions to global food security challenges while raising ethical, health, and ecological concerns. This literature review critically examines the advancements in genetically modified organisms (GMOs) and their regulatory frameworks, emphasizing their dual role in enhancing agricultural productivity and posing potential risks. Foundational studies highlight biotechnology’s ability to create herbicide-tolerant and insect-resistant crops, significantly reducing reliance on chemical pesticides. However, concerns about biodiversity loss, superweeds, and the long-term effects of GMOs remain pivotal in public debates. Emerging gene-editing techniques, such as CRISPR-Cas9, have revolutionized the field, enabling precise genomic modifications. This review identifies the need for adaptive regulatory frameworks to address the unique challenges posed by genome editing. Comparisons between traditional GMOs and gene-edited organisms reveal gaps in current governance, particularly in ensuring environmental sustainability and public trust. The role of public perception and transparent communication is underscored as critical to the acceptance and integration of GM technology. Moreover, the implications of regulatory disparities across regions, particularly between the European Union and other global markets, highlight the complexities of fostering innovation while maintaining safety and equity. This review advocates for balanced regulatory approaches that consider both safety and non-safety assessments, fostering a robust discourse on GMOs’ role in addressing food security, sustainability, and societal well-being. By aligning innovation with ethical and ecological considerations, this research contributes to understanding the intricate dynamics shaping agricultural biotechnology.